Acculturation of Javanese and Chinese Culture in Rural Tourism in Desa Wisata Besani - Yulius, Kevin Gustian (Centre for Tourism Studies and Journal Publication of Sekolah Tinggi Pariwisata Mataram, 2023)
The research paper investigates the cultural exchange between Javanese and Chinese traditions in rural tourism at Desa Wisata Besani, Central Java. Rural tourism has become popular among international travelers seeking authentic experiences and sustainable community engagement. Desa Wisata Besani, known as the